To translate or not to translate dialects in subtitling? The case of Pif’s La mafia uccide solo d’estate (Altre Modernità, 2022)
The difficulty of translating dialects has been extensively studied over the years, firstly by scholars who focused on the (un)translatability of dialects in literature, and more recently by an increasing number of academics who have been investigating the issue within the field of audiovisual translation, both in dubbing and in subtitling. This study aims to analyse the strategies used in subtitling to translate into English the Sicilian dialect spoken in the Italian film La mafia uccide solo d’estate, directed by Pif in 2013. In this film, the use of dialect is not simply a tool to indicate the geographical origins of the characters, but it is exploited to construe their identity. Indeed, language variation is a device used purposefully to distinguish the ‘good’ characters from the ‘bad’ ones, and, as such, it is a means of identification. The results of the analysis will also be compared to those of previous studies conducted in this research area. Finally, the paper will attempt to provide some potential solutions that might be adopted in the subtitling of similar products, based on previous studies performed by the author on the original dialogues of some Hollywood films.